Scheduling with fuzzy delays and fuzzy precedences - Muthusamy, Kanesan; Chin Sung, Shao; Vlach, Milan; Ishii, Hiroaki (Fuzzy sets and systems, 2003)
A problem of scheduling jobs nonpreemptively on a single machine subject to time delay constraints and precedence constraints is considered. Time delay constraints and precedence constraints are fuzzified. Schedules are evaluated not only by their makespan but also by degrees of satisfaction with time delays and degrees of satisfaction with fuzzy precedence.